Effects of Dark Chocolate with Cacao Beverages Consumption on Lipid Profiles in Healthy Volunteers - NIn-on, Nattakan -; Sanporkha, Promluck; Hudthagosol, Chatrapa (Journal of Nutrition Association of Thailand (Online), 2020)
Ischemic heart disease is one of the leading causes of death in Thailand and annual mortality trend from this disease has significantly increased. The common risk factors for coronary artery disease among Thais include dyslipidemia, hypertension, diabetes, stress, poor eating habits. Therefore, consuming healthy foods is one way to reduce the risk of this disease. This study aimed to examine the effects of dark chocolate and cacao beverages consumption on changes in lipid profiles among healthy subjects for 4 weeks. This randomized controlled trial included an experimental group (n=23) and placebo group (n=23). Paired t-test was used to compare changes of lipid profiles from week 0 to week 4 between experimental and placebo groups, Independent t-test was used to assess the differences in lipid profiles between the two groups. Results: Triglyceride and LDL-cholesterol concentrations significantly decreased from week 0 to 4 (p<0.05), while HDL-cholesterol concentration was dramatically higher at the week 4 than week 0 (p<0.000). However, the difference in total cholesterol concentration between week 0 and week 4 was not significant (p>0.05). Moreover, change in Triglyceride and HDL-cholesterol concentrations differenced significantly in experimental group compared to placebo group (p<0.05). In conclusion, this study found an advantage of dark chocolate with cacao beverages consumption on lipid profile in healthy volunteers.